Arsenic in the soil–rice system of the Mekong River delta. Issue 3 (21st April 2023) - Dao, Hoan T.; Dinh, Van M.; Nguyen, Anh T. Q.; Dang, Quan T.; Nguyen, Hue T.; Nguyen, Muu T.; Nguyen, Duc T.; Duong, Linh H.; Nguyen, Anh Q.; Pham, Anh T. M.; Le, Trang Q.; Hoang, Trang T. T.; et al.
Abstract: Arsenic (As) in rice has been known as a worldwide human health threat that results originally from the accumulation of As in soil in many rice cultivation regions. This study aims to evaluate As levels in the soil–rice system in the Mekong River delta (MRD) with special focuses on the geographical distribution and the relation to soil physio-chemical properties. It was found that soil As contents varied from 0.3 to 15.9 mg kg −1 ( x ˜ = 7.22 ± 0.3 mg kg −1 ), whereas straw As content was about one order of magnitude lower ( x ˜ = 0.92 ± 0.1 mg kg −1 ). The content of As in grain varied from "not detectable" to 1115 µg kg −1 ( x ˜ = 73 ± 19 µg kg −1 ). Relatively similar geographical distribution patterns were observed for soil As and straw As, meanwhile grain As did not reveal a clear association with straw As and soil As. The accumulation of As in rice (straw and grain) were likely affected by various factors, but the mutual effects of soil As pool and soil properties were the most obvious. The East coastal area of the MRD has been identified as a vulnerable area to As threat. This finding suggests that in addition to the action plans to preserve coastal paddy soils from the threats of sea level rise and salt intrusion, contamination of As should also be considered.